Integrating psychological and physical assessments to obtain optimal return-to-sport outcomes after ACL reconstruction: A systematic review and network meta-analysis - Lo, C.-S.; Chen, K.-C.; Shih, J.-C.; Cheng, B.; Chao, W.-C. (Journal of Sports Sciences, 2025)
This study evaluated the relative effectiveness of using different return-to-sport (RTS) assessments to improve clinical decision-making following anterior cruciate ligament reconstruction (ACLR), focusing on physical, psychological, and subjective measures. A network meta-analysis of 12 studies (1889 participants) assessed various RTS criteria, including the Anterior Cruciate Ligament-Return to Sport after Injury (ACL-RSI) scale (psychological readiness), the International Knee Documentation Committee (IKDC) questionnaire (subjective knee function), hop test (physical function), and limb symmetry indices (LSI) for extension (EXT-LSI) and flexion (FLEX-LSI). The primary outcome was the effectiveness of these criteria in predicting successful RTS, and the secondary outcomes included dropout rates and inconsistencies in the data. The ACL-RSI scale was most effective for predicting RTS success (effect size: 1.55; 95% CI: 1.24 to 1.87). Physical tests like the hop test and LSI were moderately effective, with FLEX-LSI being the least effective. There were no significant differences in dropout rates across the RTS criteria. Sensitivity analyses confirmed the stability of these results. Findings highlight the critical role of psychological readiness in RTS outcomes. Clinicians are encouraged to adopt a multi-dimentional approach, integrating both psychological and physical assessments, to improve decision-making and reduce the risk of re-injury after ACLR.